Contribution to the adoption of the Banjul Tree Cover Resolution in the Gambia - CGIAR Research Program on Forests, Trees and Agroforestry (2021)
The Resolution aims to increase tree cover and calls for an agroforestry policy, the institutionalization of tree ownership and rights, and the prioritization of high value, locally adaptable tree species